Implementation of an ESP-32 Wi-Fi CAM & Arduino-Based Robot for IoT Surveillance - Kurniawan, Fery Andika; Rochimawati, Ima; Saddiq, Azhar; Saragih, Yuliarman; Saragih, Carolan Ignatius (Seminar Nasional Teknik Elektro, 2023)
Currently, it is impossible for border guarding personnel to constantly watch the whole border, making it difficult to monitor areas along international borders. The creation of an autonomous robot that can recognize trespassers and notify the neighborhood border security control unit has become essential to meet this need. In order to complete dangerous missions that are beyond the capability of human soldiers, many military departments have turned to robots. The Internet of Things (IoT), a night vision Pi camera, and numerous sensors have been integrated into the architecture of the spy robot platform in this study, which is based on the Raspbian operating system. This platform for surveillance robots intends to protect people's lives, minimize manual errors, and shield the nation from potential dangers. A night vision Pi camera, several sensors, and a Raspberry Pi (a small single-board computer) are all part of the system. Living object detection is done by the PIR sensor, and users are informed of it via a web server. The Pi camera simultaneously records moving objects, which are then shown on a website. Users can access the robot from a control room and direct its motion using wheel drive control buttons on the website. Additionally, the robot has sensors that can identify obstacles to help it navigate without running into anything.This spy robotbased surveillance system is adaptable to a variety of settings, including businesses, financial institutions, and shopping centers, where it may be tailored to meet particular security needs. This technology makes it possible to conduct continuous and automated surveillance, which enhances the total security measures in sensitive locations.